Effect of the Exxcellence in Clinical Research Course on Research Productivity and Quality Amongst Program Completers. (October 2015) - Eskander, Ramez N.; Osann, Kathryn
Abstract : OBJECTIVE: To evaluate the self-reported effect of the Exxcellence in Clinical Research Course on academic productivity amongst course completers. METHODS: A 26-item questionnaire was distributed to 457 individuals who completed the Exxcellence course between August 2008 and May 2013. The questionnaire focused on five domains: demographics, postgraduate education, practice information, publications–grant applications, and skills attributed to completion of the course. Descriptive statistics, bivariate and multivariate analyses were performed. RESULTS: Of 457 individuals who received the survey, 31.5% (n=144) responded. Course completers were primarily women (79.2%), white (73.6%), and reported practicing in an academic environment (76.2%). Program completers reported a mean of 9.2±7.5 publications (median impact factor of 4.2±2.4). Respondents reported that course completion was associated with better teaching of evidence-based medicine (8.2±1.5; on a 1–10 Likert scale), more confidence in teaching (7.0±2.2), and assuming a more active role as an educational leader (7.0±2.3). Individuals who completed the course in years 3 or 4 of fellowship reported a significantly greater effect on communication (6.3 compared with 5.1 on a 1–10 Likert scale; P =.023), teaching (7.7 compared with 6.8; P =.049), clinical leadership (7.6 compared with 6.6; P =.031), patient advocacy (6.5 compared with 5.4; P =.048), and respect as an educational leader (7.3 compared with 6.3; P =.034). No relationship between obstetrics and gynecology National Institutes of Health finding and publication or grant funding was identified in the cohort. CONCLUSION: Individuals who attended and completed the Exxcellence course reported a positive effect on academic productivity. Efforts should be made to increase access to this valuable resource.